EKSISTENSI PERJANJIAN ELEKTRONIK SEBAGAI ALAT BUKTI DALAM HUKUM ACARA PERDATA - Leonard Parulian (Universitas Borneo Tarakan, 2021)
ABSTRACTOne form of the Industrial Revolution 4.0 that we can recognize in everyday life is electronic commerce, namely the use of communication networks and computers to carry out business processes that are agreed upon and carried out by the parties and set forth in electronic agreements/contracts. The electronic agreement/contract is carried out on the basis of trust obtained by providing legal recognition of electronic written form in the form of an electronic signature. If there is a broken promise/default by one of the parties entering into an electronic agreement/contract with electronic document evidence signed with electronic signature as evidence, then it must be known carefully the strength of the evidence of electronic agreement on the electronic document and the method of settling the civil dispute.This study aimed to examine and analyze the strength of the evidence of electronic agreements on authentic deeds and patterns of settlement of civil case disputes submitted by the parties with evidence in the form of electronic agreements. The study used a normative juridical method with legal and conceptual approaches and primary and secondary sources of legal material.From the results of the study it can be concluded that the strength of proof of electronic documents signed with electronic signatures is contrary to the strength of proof of authentic deeds made by or in front of public officials in charge where the deed was made or by the authorized public official. In addition, related to the recognition of electronic documents in the judicial system, there is a void in procedural law because it does not regulate electronic documents as evidence but rather electronic documents in the form of decisions or indictments as appeals for cassation requests and reconsideration.Keywords: Electronic Agreement, Electronic Signature, Authentic Deed, Evidence